Short communication. Differentiation of Type-I Porcine Reproductive and Respiratory Syndrome Virus vaccines and field strains by restriction fragment length polymorphism analysis - Diez-Fuertes, F.; Vazquez, A.; Hornillos-Gumiel, L.; Simarro, I.; Castro, J. M.; Martinez-Lobo, F. J. (Spanish Journal of Agricultural Research, 2012)
<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">The use of modified live virus (MLV) vaccines is a common procedure to control porcine reproductive and respiratory syndrome virus (PRRSV) infection in the great majority of countries from America, Asia and Europe, including Spain. Current discriminatory techniques allow the detection of different MLV type-II vaccine strains. Herein we report a rapid and accurate technique aimed to discriminate between MLV type-I vaccine strains and Spanish field strains. This technique comprises a reverse transcription (RT) and nested polymerase chain reaction (nPCR) amplification of PRRSV ORF5 followed by a digestion of RT-nPCR products with two specific endonucleases, <span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPS-ItalicMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Ita<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">I and <span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPS-ItalicMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Acc<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">I. Combined utilization of <span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPS-ItalicMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Ita<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">I and <span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPS-ItalicMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Acc<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">I generates restriction fragments length polymorphisms (RFLP) patterns adequate for the differentiation of 30 Spanish field isolates, of which 12 were isolated between 1991 and 1995 and 18 between 2000 and 2003. These different RFLP patterns can be used to distinguish unequivocally between Spanish field strains of PRRSV and the three MLV type-I vaccines used in Spain: AmervacPRRS®, Pyrsvac-183® and PorcilisPRRS®.